POTENTIAL HAZARDS OF SEDIMENT IN KENDARI BAY, SOUTHEAST SULAWESI - Nur Adi Kristanto; Yogi Noviadi; Purnomo Raharjo (Marine Geological Institute of Indonesia, 2008)
Kendari bay is located in front of Kendari city. There are two harbors in the inner part of bay which very important to support economic activities such as shipping and passenger transportation. The result of coastal characteristic mapping and physical oceanography survey show various coastal morphology, vegetation, weathering processes, sedimentation, currents, and water depth and sea floor morphology. Kendari bay is an enclosed bay; the area is wide in the inner part and narrow in mouth of bay (outlet), the morphology look like a bottle’s neck. Numerous mouth rivers are concentrate around the bay. The rivers load material from land since erosion on land is intensive enough. There is indication that sediment supplies from land trough river mouth not equivalent with outlet capacity. Sediment load is trapped in the inner bay caused the outlet morphology. So high sediment rate play an important role in the process of shallow of water depth in Kendari bay. This condition make the Kendari bay is a prone area of sediment hazard due to height rate of sedimentary process. Therefore, to anticipate the hazards, precaution should be taken related to the Kendari bay as the center of activities in southeast of Sulawesi. The further survey is needed such as marine geotechnique and on land environmental to collect data, which can be used as database for development planning. Key words: Potential hazard, sediment, Kendari Bay Teluk Kendari terletak di bagian depan kota Kendari. Di bagian dalam teluk terdapat 2 pelabuhan yang sangat penting untuk menunjang kegiatan ekonomi seperti perikanan dan transportasi. Hasil pemetaan karakteristik pantai dan penyelidikan oseanografi memperlihatkan kondisi morfologi pantai, vegetasi, proses pelapukan, sedimentasi, arus, kedalaman air laut dan morfologi dasar laut. Teluk Kendari merupakan teluk tertutup yang lebar di bagian dalamnya dan sempit di bagian mulutnya dimana morfologinya terlihat seperti lehar botol. Beberapa mulut sungai terkosentrasi di sekitar teluk. Sungai bermuatan material dari daratan selama erosi didaratan cukup intensif. Hal ini mencerminkan indikasi suplai sedimen dari darat melalui muara sungai tidak sama dengan kapasitas pengeluaran. Muatan sedimen terperangkap di bagian dalam teluk dan menyebabkan terbentuknya morfologi cerobong. Tingginya muatan sedimen merupakan proses yang penting terjadinya pendangkalan di Teluk Kendari Kondisi tersebut menyebabkan Teluk Kendari cenderung merupakan daerah yang akan mengalami bahaya pendangkalan akibat tingginya proses sedimentasi. Oleh karena itu untuk menanggulagi bahaya tersebut, harus dilakukan pencegahan karena Teluk Kendari merupakan pusat kegiatan di Sulawesi Tenggara. Penelitian selanjutnya seperti pengumpulan data geoteknik kelautan dan lingkungan sangat diperlukan untuk dijadikan data dasar untuk rencana pengembangan.